3D porous carbon conductive network with highly dispersed Fe–Nx sites catalysts for oxygen reduction reaction. (5th November 2022) - Zhang, Wenxin; Liang, Zhiwei; Tian, Wensheng; Liu, Yuan; Du, Yuanzhen; Chen, Mingming; Cao, Dawei
Abstract: Intrinsic activity and reactive numbers are considered two important factors in oxygen reduction reaction (ORR) catalysts. Herein, we report the rational design and synthesis of a strongly coupled hybrid material comprising of FeZn nanoparticles (FeZn NPs) supported by a three-dimensional carbon conductive network (FeZn NPs@3D-CN) for increased ORR performance. Fe–N–C sites can offer high intrinsic activity owing to the unique bonding and oxygen vacancies, and the carbon conductive network facilitating the exposure to active sites, and increasing electron transport. Because of the synergetic effect of the conductive networks containing Fe–N–C and polyaniline, the catalysts exhibited ORR activity in an alkaline medium via a four-electron transfer process. FeZn NPs@3D-CN exhibited outstanding performance with a limited current density (6.2 mA cm −2 ), the Tafel slope (81.19 mV dec −1 ), and stability (23 mV negative shift after 2000 cycles), which were superior to those of 20% Pt/C (5.7 mA cm −2, 75.1 mV dec −1, 36 mV negative shift after 2000 cycles). This research highlights the effect of conductive networks expanding pathways and reducing the resistance of mass transport, which is a facile method to generate superior ORR electrocatalysts.